Use of Artemia Meal as a Protein Supplement in Broiler Diet - Zarei, A.; Shivazad, M.; Mirhadi, A. (International Journal of Poultry Science, 2006)
Different levels of protein from two kind of Artemia meal include Artemia meal from Urmia lake and Artemia meal from earth ponds beside Urmia lake with levels of 0, 25, 50, 75, 100 percent replaced to prue fish meal protein. The experimental design was completely randomized with factorial method, include 10 treatments and 3 repetitions that in each repetition there were 10 one day-old male broilers from Ross 308 strain. This experiment was performed in 7 weeks and during and end of it, traits that related to broiler performance and carcass, was measured and analyzed. Results showed that effect of kind of Artemia meal and effect of level of protein replacement wasn`t significant for feed intake. But interaction between this two was significant for this trait (P< 0.05). The highest feed intake belong to Urmia lake Artemia meal treatment with 50% level of replacement and the lowest feed intake related to treatment of without Artemia meal (contain 5% fish meal). For body weight gain and feed conversion ratio, effect of kind of Artemia meal and effect of level of protein replacement and effect of interaction between this two weren`t significant. These effects weren`t significant for all dressing traits and gastro intestinal parts exception for femur percent that treatment of without Artemia meal (contain 5% fish meal) had a lowest percent to comparison with other treatments for this traits.